2019
DOI: 10.1098/rstb.2019.0219
|View full text |Cite
|
Sign up to set email alerts
|

Anthropocene refugia: integrating history and predictive modelling to assess the space available for biodiversity in a human-dominated world

Abstract: During periods of strong environmental change, some areas may serve as refugia, where components of biodiversity can find protection, persist and potentially expand from should conditions again become favourable. The refugia concept has previously been used in the context of climatic change, to describe climatically stable areas in which taxa survived past Quaternary glacial–interglacial oscillations, or where they might persist in the future under anthropogenic climate change. However, with the recognition th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…However, the identified areas could be seen as "future climate refuges" for these species. Identifying areas that are most likely to persist under adverse climate change conditions in the future is important for anticipating the complex impacts that climate change will have on ecosystems and societies (Monsarrat et al, 2019). The socio-ecological implications of some species that recolonize part of their historical niche or occupy new areas should be carefully considered, in particular for species with a high socio-ecological interest such as small pelagic fishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identified areas could be seen as "future climate refuges" for these species. Identifying areas that are most likely to persist under adverse climate change conditions in the future is important for anticipating the complex impacts that climate change will have on ecosystems and societies (Monsarrat et al, 2019). The socio-ecological implications of some species that recolonize part of their historical niche or occupy new areas should be carefully considered, in particular for species with a high socio-ecological interest such as small pelagic fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Such areas can act as sources of re-colonization when environmental conditions improve and often have long-lasting imprints on species distributions. We argue that identifying climate refuges can provide essential knowledge to improve the SPF management by identifying key areas for conservation of these species and potential for re-expansions both today and in the future (Monsarrat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By this, our study urges scientists and authorities to aim the conservation effort at areas with overlaps among PAs and climate refugia, characterized simultaneously by high diversity and EDGE scores (including the 11 taxa with the highest EDGE score), as well as serving as mixed-endemism centres. These areas are qualified as future climate refugia and may actually constitute Anthropocene refugia (Monsarrat et al, 2019). By doing so, this 'climate-smart', cost-effective conservation prioritization planning will allow the preservation of evolutionary heritage, trait diversity and future services for human well-being (Veron et al, 2019).…”
Section: Conclusion -Conservation and Management Implicationsmentioning
confidence: 99%
“…Humanity has to address efforts to stop "biological annihilation" based on population decline and species extirpation, which has negative cascading consequences on ecosystem functioning and services (Ceballos et al, 2017;Monsarrat et al, 2019). The loss of biodiversity is the result of several drivers and their interactions, including land-use/cover-change (LUCC), climate change (CC), species invasion and disease (Brook et al, 2008;Sala et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of biodiversity is the result of several drivers and their interactions, including land-use/cover-change (LUCC), climate change (CC), species invasion and disease (Brook et al, 2008;Sala et al, 2000). However, the effects of CC on the LUCC process and their combined effects on biodiversity are uncertain (Monsarrat et al, 2019;Oliver and Morecroft, 2014). In the tropics, LUCC is expected to be the major force of change, but other studies have suggested that CC may play an important role, particularly for mammals (Paniw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%